DEVELOPING PMRI LEARNING ENVIRONMENT THROUGH LESSON STUDY FOR PRE-SERVICE PRIMARY SCHOOL TEACHER - Anna Fauziah; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Somakim Somakim (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
Teachers’ pedagogical ability contributes significantly to their process and learning performance. To improve it, a development process is needed as long as they are still having their process of education or they are still teacher students. This study aimed to develop a valid and practical PMRI learning environment through lesson study which had a potential effect on improving the pedagogical abilities of pre-service primary school teachers. A design research method of development study type was used in this study consisting of three phases, namely the preliminary, development or prototyping phase, and assessment phase. The research subjects were 32 students of Primary School Teacher Education of Sriwijaya University. The data were collected using walkthrough, observation, documentation, questionnaires, interviews, and tests. The study produced a learning environment with a valid and practical Campus-School (CS) model and had a potential effect on improving teacher students' pedagogical ability. The learning environment was in the form of training on campus and implementation in schools. Based on the data analysis, the learning environment was able to produce pre-service primary education teachers understanding the PMRI through lesson study and design PMRI learning tools through a lesson study.